First molecular identification of the trematode Maritrema bonaerense Etchegoin & Martorelli, 1997 (Plagiorchiida, Microphallidae) from its intermediate hosts, the gastropod Heleobia australis (d'Orbigny, 1835) (Littorinimorpha, Cochliopidae) and the crab - Martinez, Lorena Evangelina (2023)
The genus Maritrema Nicoll, 1907 (Platyhelminthes, Trematoda, Plagiorchiida, Microphallidae) comprises cosmopolitan species that predominantly parasitize birds. Although approximately 65 species have been described worldwide, including 6 for Argentina, molecular data referring to Maritrema species are still scarce worldwide, especially in South America. Unfortunately, this lack of references for nucleotide sequences is an obstacle to understanding the taxonomy and life cycles of trematodes, and impedes advancing our studies on the phylogeny and geographical distribution of these parasites. For that reason, we performed the molecular study of developmental stages of Maritrema bonaerense: cercariae (collected from the snail first intermediate host Heleobia australis, inhabiting Mar Chiquita lagoon) and metacercariae (collected from the crab second intermediate host Neohelice granulata, inhabiting Mar Chiquita lagoon and San Antonio Oeste, Argentina). The accordance between the ITS2 sequence of M. bonaerense cercaria from the snail H. australis and the sequences of metacercariae from the crab N. granulata was 100%, supporting previous findings of the life cycle of M. bonaerense based on morphological data. All Maritrema species are included in a monophyletic and well-supported clade. Maritrema bonaerense grouped more closely with Maritrema gratiosum. These findings contribute to the knowledge of digeneans in coastal marine ecosystems.